23.3: Invited Paper: Upgrading Self‐Aligned Imprint Lithography (SAIL) in Preparation for Roll‐to‐Roll Manufacturing of Large‐Sized High‐Performance Flexible Electronics. Issue 1 (1st July 2013) - Kim, Han‐Jun; Elder, Richard; Vornbrock, Alejandro de la Fuente; Hoffman, Randy; Holland, Edward; Jeans, Albert; Luo, Hao; Maltabes, John; Mei, Ping; Perlov, Craig; Taussig, Carl; Morrison, Neil
Abstract Self‐aligned imprint lithography (SAIL) is currently being upgraded to a next stage to better address the needs for roll‐to‐roll compatible manufacturing of large‐sized flexible OLED display backplanes. Cu and oxide semiconductors are preferred choices of materials, and control of process and yield becomes even more important an issue.